Erosion–corrosion behavior of aluminum in a 50°C ethylene glycol aqueous solution simulating cooling water in HVDC transmission. Issue 12 (3rd August 2021) - Tian, Yingfu; Li, Huixi; Wang, Shengping; Fan, Youping
Abstract: The erosion–corrosion of aluminum in a 50 °C ethylene glycol aqueous solution (EGAS) was studied. Compared with that in deionized water, the corrosion of aluminum in an EGAS was inhibited to a certain extent. The corrosion potential, corrosion current, and charge transfer impedance of aluminum changed from −1.5776 V, 380.4 nA cm −2, and 1.924 × 10 −4 Ω cm −2 in deionized water to −1.3127 V, 285.5 nA cm −2, and 4.041 × 10 −4 Ω cm −2 in a 45.3 vt% EGAS, respectively. Ethylene glycol did not ionize in deionized water and the ionic conductivity of the EGAS was low, effectively restraining the corrosion of aluminum. However, a test with aluminum in an EGAS after long‐term storage (9 days) showed that ethylene glycol gradually oxidized to glycolic acid, oxalic acid, and other substances, which slowly corroded the aluminum surface. Analysis results showed that the corrosion products on the surface of aluminum were Al(OH)3 and Al2 O3 . The pitting hole formation mechanism of aluminum occurs via an aluminum–alcohol phase formed on the aluminum surface, which can inhibit the dissolution of the oxide film. Therefore, a suitably concentrated EGAS with a high heat capacity and low ionic conductivity similar to that of deionized water can be used as a coolant in airtight valve cooling systems for high‐voltage direct‐current transmission. Abstract : Compared with that in deionized water, the erosion‐corrosion of aluminum in a 50 °C ethylene glycol aqueous solution (EGAS) was inhibited to a certain extent. Therefore, in order to solve the problems of radiatorcorrosion and grading electrode scaling, a suitably concentrated EGAS with a high heat capacity and low ionic conductivity similar to that of deionized water can be used as a coolant in valve cooling systems for high‐voltage direct‐current transmission.